Pragmatic modernism - Schoenbach, Lisi (New York Oxford Oxford University Press, 2012)
'Pragmatic Modernism' traces an alternative strain of modernism influenced by pragmatist philosophy and characterized by its commitment to gradualism, continuity, and habit rather than spectacular events and radical rupture.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: James, Henry -- 1843-1916 -- Philosophy; Stein, Gertrude -- 1874-1946 -- Philosophy; Modernism (Literature); American literature -- History and criticism. -- 20th century; American literature -- History and criticism. -- 19th century; Modernism (Aesthetics); Pragmatism; Habit (Philosophy); Social change -- Philosophy